FAIM2 Promotes Non-Small Cell Lung Cancer Cell Growth and Bone Metastasis by Activating the Wnt/β-Catenin Pathway - She, Kelin; Yang, Wensheng; Li, Mengna; Xiong, Wei; Zhou, Ming (Frontiers in Oncology, 2021)
Aim Bone metastasis is the major reason for the poor prognosis and high mortality rate of non-small cell lung cancer (NSCLC) patients. This study explored the function and underlying mechanism of Fas apoptotic inhibitory molecule 2 (FAIM2) in the bone metastasis of NSCLC. Methods Samples of normal lung tissue and NSCLC tissue (with or without bone metastasis) were collected and analyzed for FAIM2 expression. HARA cells that overexpressed FAIM2 and HARA-B4 cells with FAIM2 knockdown were tested for proliferation, migration, invasion, anoikis, and their ability to adhere to osteoblasts. Next, we investigated whether FAIM2 might facilitate bone metastasis by regulating the epithelial mesenchymal transformation (EMT) process and Wnt/β-catenin signaling pathway. Finally, an in vivo model of NSCLC bone metastasis was established and used to further examine the influence of FAIM2 on bone metastasis. Results FAIM2 was highly expressed in NSCLC tissues and NSCLC tissues with bone metastasis. FAIM2 expression was positively associated with tumor stage, lymph node metastasis, bone metastasis, and a poor prognosis of NSCLC. FAIM2 up-regulation promoted HARA cell proliferation, migration, and invasion, but inhibited cell apoptosis. FAIM2 knockdown in HARA-B4 cells produced the opposite effects. HARA-B4 cells showed a stronger adhesive ability to osteocytes than did HARA cells. FAIM2 was found to be related to the adhesive ability of HARA and HARA-B4 cells to osteocytes. FAIM2 facilitated bone metastasis by regulating the EMT process and Wnt/β-catenin signaling pathway. Finally, FAIM2 was found to participate in regulating NSCLC bone metastasis in vivo. Conclusions FAIM2 promoted NSCLC cell growth and bone metastasis by regulating the EMT process and Wnt/β-catenin signaling pathway. FAIM2 might be useful for diagnosing and treating NSCLC bone metastases.